ASSESSMENT OF PHYSICO-CHEMICAL AND RHEOLOGICAL PROPERTIES OF FUNCTIONAL ICE CREAM INFUSED WITH RED SEAWEED (KAPPAPHYCUS ALVAREZII) CONCENTRATE AS A STABILIZER - P. Sivakumar; M. Dharani (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Ice cream, a well-known frozen delicacy, is prone to fluctuations in both physical and sensory characteristics in spite of its complex composition. Many highly processed stabilizers and emulsifiers that are chemically purified and modified, individually or in combination, were used in food industries to develop a product with desired physical, chemical and textural stability. In this study, the viability of minimally processed hydrothermal extract of red seaweed (Kappaphycus alvarezii) was tested to replace sodium alginate in ice cream. The functional carrot flavoured ice cream stabilized by 0.4%w/w sodium alginate and 0.1%w/w glycerol monostearate was taken as control. The stabilizer was replaced by Red seaweed (Kappaphycus alvarezii) extract at concentration of 0.5% (S1) and 1.0% w/v (S2). The addition of red seaweed extract at 1.0% w/v (S2) in ice cream increased the overrun from 46% to 57% (S2) in the batch freezer and melting resistance was also notably decreased from 1.90 to 0.62 (S2) g/min. Significance of the research was that minimally processed extracts of red seaweed (Kappaphycus alvarezii) are highly effective to replace processed stabilizer and emulsifiers used in food industries.